In-Depth Analysis of the Impact of Different Serum-Free Media on the Production of Clinical Grade Dendritic Cells for Cancer Immunotherapy - Calmeiro, João; Mendes, Luís; Duarte, Iola F.; Leitão, Catarina; Tavares, Adriana R.; Ferreira, Daniel Alexandre; Gomes, Célia; Serra, João; Falcão, Amílcar; Cruz, Maria Teresa; Carrascal, Mylène A.; Neves, Bruno Miguel (Frontiers in Immunology, 2021)
Dendritic cell (DC)-based antitumour vaccines have proven to be a safe approach, but often fail to generate robust results between trials. Translation to the clinic has been hindered in part by the lack of standard operation procedures for vaccines production, namely the definition of optimal culture conditions during ex-vivo DC differentiation. Here we sought to compare the ability of three clinical grade serum-free media, DendriMACS, AIM-V and X-VIVO 15, alongside with fetal bovine serum-supplemented Roswell Park Memorial Institute Medium (RPMI), to support the differentiation of monocyte-derived DCs (Mo-DCs). Under these different culture conditions, phenotype, cell metabolomic profiles, response to maturation stimuli, cytokines production, allogenic T cell stimulatory capacity, as well as priming of antigen-specific CD8+ T cells and activation of autologous natural killer (NK) cells were analysed. Immature Mo-DCs differentiated in AIM-V or X-VIVO 15 presented lower levels of CD1c, CD1a and higher expression of CD11c, when compared to cells obtained with DendriMACS. Upon stimulation, only AIM-V or X-VIVO 15 DCs acquired a full mature phenotype, which supports their enhanced capacity to polarize T helper cell type 1 subset, to prime antigen-specific CD8+ T cells and to activate NK cells. CD8+ T cells and NK cells resulting from co-culture with AIM-V or X-VIVO 15 DCs also shown superior cytolytic activity. 1H nuclear magnetic resonance-based metabolomic analysis revealed that superior DC immunostimulatory capacities correlate with an enhanced catabolism of amino acids and glucose. Overall, our data highlight the impact of critically defining the culture medium used in the production of DCs for clinical application in cancer immunotherapy. Moreover, the manipulation of metabolic state during differentiation could be envisaged as a strategy to enhance desired cell characteristics.